WHAT IS IT TO BE A PERSON? - TAHMASBI, Mohammad Reza (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
I will deal with the synchronic question of persons to clarify the necessary and sufficient conditions for being a person. Having reflexive self-consciousness is both the necessary and sufficient conditions for being a person. I discuss the relationship between having reflexive self-consciousness and the other properties which uniquely belong to persons ‘i.e.,’ being a moral agent, being a rational agent and having free will. A problem arises when one defines a person based on having reflexive self-consciousness. “Is a sleeping human being still a person?” To resolve the problem, I will appeal to Aristotle’s distinction between first and second potentialities.